Modification of low density polyethylene for manufacturing of oxo-biodegradable films - Machlarz, R.; Heneczkowski, M. (Polimery, 2014)
The effect of various additives on oxo-biodegradation of films made of low density polyethylene (PE-LD) compositions has been investigated. Twelve compositions were made with varying contents of a prodegradant. Masterbatches acting as a prodegradant consisted of: PE-LD, iron(II) stearate (FeSt2) as a catalyst for decomposition, ethylene-propylene-diene copolymer Royaltuf® 485 (Roy) as an agent reducing ferric ions, quaternary ammonium salt modified bentonite (ZR2) as a nanofiller, and compatibilizer Fusabond® E226 (Fus). Reference material consisted of PE-LD film which was not supplemented with the above additives. Assessment focused on the impact of nanofiller and copolymer on functional properties and oxo-biodegradation processes in the obtained films. The impact was assessed by taking into account changes in external appearance, mechanical properties, location and incidence of bands in infrared spectra, values of surface free energy (SFE) and effect of microorganisms on the film surfaces. The findings showed that addition of ZR2 resulted in improved initial strength characteristics of the films, and iron stearate accelerated the degradation process in the polyethylene whereby its hydrophilicity and susceptibility to microorganisms were increased. Addition of Roy promoted acceleration of oxo-degradation process.